Disagreement and Evidential Attenuation - Lasonen-Aarnio, Maria (Noûs (Bloomington, Indiana), 2013)
What sort of doxastic response is rational to learning that one disagrees with an epistemic peer who has evaluated the same evidence? I argue that even weak general recommendations run the risk of being incompatible with a pair of real epistemic phenomena, what I call evidential attenuation and evidential amplification. I focus on a popular and intuitive view of disagreement, the equal weight view. I take it to state that in cases of peer disagreement, a subject ought to end up equally confident that her own opinion is correct as that the opinion of her peer is. I say why we should regard the equal weight view as a synchronie constraint on (prior) credence functions. I then spell out a trilemma for the view: it violates what are intuitively correct updates (also leading to violations of conditionalisation), it poses implausible restrictions on prior credence functions, or it is non-substantive. The sorts of reasons why the equal weight view fails apply to other views as well: there is no blanket answer to the question of how a subject should adjust her opinions in cases of peer disagreement.